Pharmacogenetic study focused on fluoxetine pharmacodynamics in children and adolescent patients: impact of the serotonin pathway. Issue 11 (November 2016) - Mas, Sergi; Blázquez, Ana; Rodríguez, Natalia; Boloc, Daniel; Lafuente, Amalia; Arnaiz, Joan A.; Lázaro, Luisa; Gassó, Patricia
Abstract : Objective: Pharmacogenetic studies of fluoxetine in children and adolescents are scarce. After reporting the effect of genetic variants in genes related to the fluoxetine pharmacokinetics on clinical response in a pediatric population, we now evaluate the impact of genetic markers involved in its pharmacodynamics. Patients and methods: The assessment was performed in 83 patients after 12 weeks of fluoxetine treatment. The genetic association analysis included a total of 316 validated single nucleotide polymorphisms in 45 candidate genes involved in six different pathways. Results: Clinical improvement after treatment with fluoxetine in our pediatric population was associated significantly with two polymorphisms located in genes related to the serotonergic system: the 5-hydroxytryptamine receptor 1B ( HTR1B ) and the tryptophan 5-hydroxylase 2 ( TPH2 ). Conclusion: Although a wide range of candidate genes related to different pathways were assessed, the results show that genetic markers directly related to serotonin have an important effect on fluoxetine response. Abstract : Supplemental Digital Content is available in the text.